Effects of nursing comfort care integrating with the daily Islamic rituals on comfort among mechanically ventilated Muslim patients: A randomized clinical trial - Junaidy Suparman Rustam; Waraporn Kongsuwan; Luppana Kitrungrote (Tehran University of Medical Sciences, 2021)
Background & Aim: Most mechanically ventilated patients reported decreasing comfort during their treatments, especially in Muslim patients. Nursing comfort care needs to be addressed by integrating the principles of Islamic daily rituals to fulfill the spiritual need and also to promote holistic comfort of Muslim patients with mechanical ventilation. This study aimed to investigate the effect of nursing comfort care integrating with the Islamic daily rituals on comfort among mechanically ventilated Muslim patients. Methods & Materials: A pretest-posttest with a control group design was used. Fifty-six participants recruited from intensive care units of three public hospitals in Indonesia were randomly assigned into either the experimental group (n=28) or control group (n=28) by matching technique based on gender, age, and duration using a ventilator. Those in the experimental group received nursing comfort care developed based on Kolcaba's Theory of Comfort integrating with the Islamic daily rituals while those in the control group received usual care. Comfort was measured on the first day before receiving the intervention, and on the second day after the intervention was completed by using Comfort Questionnaire for Mechanically Ventilated Patients (CQMVP). Results:  Data analysis by using an independent t-test found there is no significant difference in data between the experimental group and control group at baseline (t = .134, p .894). The mean comfort score of patients in the experimental group after receiving the intervention was significantly higher than those in the control group (t=6.70, p<.05).   Conclusion:  Nursing comfort care integrated with Islamic daily rituals increased comfort in Muslim patients while receiving mechanical ventilation. Thus, this nursing comfort care program can be recommended to use in practice.